Strategies Managing Smart Packaging For Food Application - Evita Riviani Achmadi (Universitas Veteran Bangun Nusantara, 2023)
Abstract Background: Traditional packaging will be shifting to innovative packaging due to significantly growing to new trend following increasing consumers awareness correlated with food safety, quality and traceability. Consumers need real time information about food condition which define shelf life such as physiological process, chemical process, physical process, microbiological aspect and infestation. Through the proper application of packaging system, this requirement can be managed to give functional properties to packaging such as prolonged shelf life, control, identification and monitoring food safety and quality. Smart packaging is the part of innovative packaging which give synergism functional properties between active and intelligent packaging. System, material and technologies which applied in smart packaging will bring advantage to fulfill consumer needed.Scope and approach: The application of smart packaging in the food industry requires an appropriate, effective and efficient mapping and management strategy so that the benefits can be felt in a sustainable manner. This mapping and management strategy can be carried out by assessing the main factors that support smart packaging applications in food products. Factors that need to be reviewed more deeply include i) understanding the difference between innovative and traditional packaging; ii) the concept of smart packaging as part of innovative packaging; iii) consumer perspective on smart packaging; iv) smart packaging function; v) the challenge of implementing smart packaging.Key finding and conclusion: Implementation smart packaging using appropriate strategy will have positive impact on supply chain sustainability, quality improvement, safety, traceability, authentication, integration and can be used as an alternative to the use of food preservatives and additives. Strategy implementation must be considerate smart packaging concept which bring consumer perspective about benefit and value adding functional properties of smart packaging. Smart packaging has a functional value that can be categorized based on system, material and techniques. The selection of packaging materials, technology and packaging techniques must be suitable with characteristics and categories of food to provide method which can manage and maintain smart packaging in food application. Application smart packaging in food has challenges which arise from a number of obstacles encountered, including difficulties in increasing production scale, incorporation of materials, devices and systems into packaging, determining commercial performance indications, increasing production costs, food safety related to the contact of packaging materials with food products and consumer acceptance. These obstacles can be overcome properly if the management strategy for implementing smart packaging is planned in a comprehensive manner so that parties involved in the food supply chain (consumers, distributors and producers) experience optimal benefits Keyword: smart packaging, intelligent packaging, active packaging